STRATEGI PENYUSUNAN E-BOOK BERPENDEKATAN ETNOPEDAGOGI UNTUK MENINGKATKAN CULTURAL AND CIVIC LITERACY - Jody Setya Hermawan; Yoga Fernando Rizqi; Siti Nuraini; Desvyta Shelzalia Indra; Adelia Ananda SP (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development strategy for ethnopedagogical e-books is an important initiative that aims to improve students' cultural literacy by integrating local wisdom values into the educational framework. Ethnopedagogy is defined as an approach that emphasises local culture, traditions, and life experiences as fundamental elements for effective teaching and learning. This process begins with the identification of relevant cultural components, including folklore, customs, regional dialects, and traditional values that are relevant to students. These components are seamlessly integrated into the e-book content, in accordance with the competencies listed in the national curriculum. To increase student engagement, the e-book is created with interactive features that combine visual, audio, and video media, thereby enriching the cultural understanding experience. The application of contextual and communicative language facilitates a closer relationship between students and the material presented. Additionally, the e-book includes reflective and creative activities, such as cultural projects, documentation of family traditions, or the creation of inspiring folk tales. This method makes the learning experience meaningful, enjoyable, and relevant, while still appreciating and taking pride in cultural heritage. As a result, ethnopedagogical e-books not only improve academic understanding but also contribute to the development of students' character and cultural identity in the digital age.